2007
DOI: 10.1007/s10551-007-9412-6
|View full text |Cite
|
Sign up to set email alerts
|

The Investment Performance of Socially Responsible Investment Funds in Australia

Abstract: investment performance, SRI funds, capital asset pricing model,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 37 publications
(71 reference statements)
4
65
0
5
Order By: Relevance
“…However, social screening for SRI is incompatible with the modern portfolio theory. Modern portfolio theories suggest that any restrictions imposed on a portfolio's selection results in inferior performance (Das and Rao 2013;Jones et al 2008;Reyes and Grieb 1998). The underperformance of the SRI fund might be causing a smaller diversification effect.…”
Section: Resultsmentioning
confidence: 99%
“…However, social screening for SRI is incompatible with the modern portfolio theory. Modern portfolio theories suggest that any restrictions imposed on a portfolio's selection results in inferior performance (Das and Rao 2013;Jones et al 2008;Reyes and Grieb 1998). The underperformance of the SRI fund might be causing a smaller diversification effect.…”
Section: Resultsmentioning
confidence: 99%
“…In the Australian context, there are relatively few studies such as those of (Bauer et al, 2006;Tippet, 2001;Cummings, 2000) which show that the performance of SRI is not significantly different with conventional investments while other studies (Jones et al, 2008) found SRI to be underperforming in the Australian context. None of these studies, however, have focused on the linkages or spill-over between SRI markets.…”
Section: Brief Review Of the Literaturementioning
confidence: 98%
“…Moreover, highly profitable and leveraged firms feel free to contribution to CSR and increase their reputation. On the other hand, many studies found positive (Ruf, Muralidhar, Brown, Janney, & Paul, 2001;Vitezic, 2011;Waddock & Graves, 1997) or negative (Jaggi & Freedman, 1992;Jones, Van der Laan, Frost, & Loftus, 2008;Makni, Francoeur, & Bellavance, 2009) relation between profitability and CSR level. Based on the discussion above, the fifth, sixth, and seventh hypotheses are given below:…”
Section: Research Purpose and Hypothesesmentioning
confidence: 99%